A possible role of astrocytes in contextual memory retrieval: An analysis obtained using a quantitative framework - Tewari, Shivendra; Parpura, Vladimir (Frontiers in Computational Neuroscience, 2013)
The hippocampus is central to our understanding of memory formation and retrieval. Its CA1 region is known for encoding contextual memory. Here, using a computational approach, which embeds existing physiological data, we propose a particular role of astrocytes in contextual memory retrieval. We provide a quantitative framework under which the astrocyte modulates the firing of a context-associated CA1 pyramidal neurons, resulting in a prominent tuning of neurons to a delta rhythm. Using the very framework, we further studied astrocytic function in the modulation of neuronal firing under pathological conditions, i.e., during astrocytic induction of epileptiform discharge in CA1 pyramidal neurons. Thus, we provide a quantitative framework that would aid understanding of the Schaffer collateral-CA1 tripartite synapse in health and disease.